Growth, Biomass Productivity and Energy Characteristics of Prosopis juliﬂ ora (Sw.) DC. and Leucaena leucocephala (Lam.) De Wit in Afar Region, Ethiopia - Ali, Ahmed Seid; Tudsri, Sayan; Rungmekarat, Sarawut; Kaewtrakulpong, Kriengkri (Agriculture and Natural Resources, 2013)
The performance of Prosopis juliﬂ ora and Leucaena leucocephala was investigated at plant spacings of 1 × 0.5, 1 × 1, 1 × 1.5, 1 × 2 and 1 × 2.5 m corresponding to a tree density of 20,000, 10,000, 6,666, 5,000 and 4,000 ha−1, respectively, to identify the most suitable plant spacing for the optimum biomass harvest per unit area. The overall performance of L. leucocephala was superior to P. juliﬂ ora under most parameters measured, except for the caloriﬁ c value. The performance of both species in terms of the plant height, stem diameter and number of trunks was affected by the population density at age 6 mths and there were signiﬁ cant increases at wider spacings (1 × 2 and 1 × 2.5 m) when the age advanced to 12 mth. There were signiﬁ cant differences in the biomass production per tree and better total above ground biomass results were obtained with plantings at wider spacings at both 6 and 12 mth of age. However, the total above ground biomass yield per hectare of both species increased markedly with increasing plant density at both 6 and 12 mth of age and this revealed that both species can be grown at closer spacing (1 × 0.5 m).